Abundance Of Parkia Biglobosa And Woody Species Composition In Protected And Unprotected Forest Of Southern Kano State Nigeria - Lawan, Mujitapha (2019)
This research aimed to determine the abundance of Parkia biglobosa and woody plants composition between protected Falgore Game Reserve (FGR) and unprotected Massu-Dagora Forest (MDF) in Southern Kano, Nigeria. The main objectives of the research were to estimate the abundance of P. biglobosa between the two forest types; to compare the woody plants diversity and composition between the two forest types and to study the correlation between environmental factors of the study areas with abundance of P. biglobosa. A total of 30 randomly stratified enumeration plots with quadrat size 20m x 10m square each were established in different location from each forest. A total of 5484 stems of woody plants belonging to 24 families were recorded, where 55 genera were found in FGR while 42 genera were recorded from MDF. Higher species number were recorded from FGR with 71 species while 50 species from MDF. The dominant species in FGR were Guiera senegalensis with (236, 6.9%) individual, followed by Cassia singueana (168, 4.9%) and Anogeissus leiocarpus (133, 3.9%). Dominant species in MDF was Combretum glutinosum with (171, 8.2%) total number of individuals followed by G. senegalensis with (147, 7.1%) and C. sieberiana (134, 6.5%). The diversity (species richness) of woody plants was higher in FGR with Shannon index value of (H’= 3.948) when compared with MDF with (H’= 3.515) this showed that the two forest types differed in species richness and composition.